Engineering intrinsic flexibility in polycrystalline perovskite film by grain boundary stitching for high mechanical endurance. (1st June 2022) - Fahim, Muhammad; Firdous, Irum; Tsang, Sai-Wing; Daoud, Walid A.
Abstract: A metal halide perovskite (MHP) thin film processed at low temperature is uniquely suited for flexible perovskite solar cells owing to its characteristic low formation energies. However, the intrinsic brittleness (low toughness) of MHP crystals restrict the mechanical endurance, particularly in polycrystalline MHP films enriched with grain boundaries (GBs). To address this issue, a mechanically flexible film of highly crystalline MHP is achieved via a novel soft stitching strategy of GBs, in which a multifunctional sticky elastomer (s-ELA) is used to connect the rigid crystallite grains. The s-ELA also acts as a scaffold in the MHP crystallization process, thereby passivating the structural defects at GBs and improving charge transport properties. This soft-rigid structural design endows excellent mechanical endurance and preserves the morphology after 10, 000 deformation cycles of bending at radii as small as 2 mm and stretching of 20%. Furthermore, the hydrophobicity of the s-ELA protects against ingress of moisture and oxygen. The soft-rigid device design represents a new approach towards wearable MHP films with good mechanical endurance, charge transport properties and environmental stability. Graphical Abstract: Multifunctional sticky elastomer acts as scaffold in the perovskite crystallization process and passivator of grain boundaries of the polycrystalline perovskite film, thereby suppressing the structural defects and stitching the rigid perovskite grains via soft bridging through physical adhesion and dynamic bonding, which provides mechanical robustness and protection against environmental erosion. ga1 Highlights: Introducing intrinsic flexibility in polycrystalline perovskite film via soft-rigid strategy. Soft sticky elastomer act as template to control nucleation and crystal growth. Soft-rigid design preserves the morphology after 10, 000 deformation cycles. Device shows high endurance at 20% stretching retaining PCE of 81% after 10, 000 cycles. Sticky elastomer protects against ingress of moisture/oxygen due to high hydrophobicity.